2019
DOI: 10.1038/s41598-019-54439-w
|View full text |Cite
|
Sign up to set email alerts
|

PedMap: a pediatric diseases map generated from clinical big data from Hangzhou, China

Abstract: Epidemiological knowledge of pediatric diseases may improve professionals’ understanding of the pathophysiology of and risk factors for diseases and is also crucial for decision making related to workforce and resource planning in pediatric departments. In this study, a pediatric disease epidemiology knowledgebase called PedMap (http://pedmap.nbscn.org) was constructed from the clinical data from 5 447 202 outpatient visits of 2 189 868 unique patients at a children’s hospital (Hangzhou, China) from 2013 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In this study the pediatric malaria weight of malaria was 51.2 %. In 2015 malaria was responsible for 45 % of outpatient visits and 56 % of pediatric admissions in Mozambique [2] consistency with these results. A study in Manhiça, a rural area in the south of Mozambique in 2008 [22] indicated 30.5 % had malaria, lower than the results of the present study and, this can be related to environmental conditions since the south of Mozambique is more arid.…”
Section: Malaria Risk Mapping I Analytical Hierarchical Process and C...supporting
confidence: 78%
See 1 more Smart Citation
“…In this study the pediatric malaria weight of malaria was 51.2 %. In 2015 malaria was responsible for 45 % of outpatient visits and 56 % of pediatric admissions in Mozambique [2] consistency with these results. A study in Manhiça, a rural area in the south of Mozambique in 2008 [22] indicated 30.5 % had malaria, lower than the results of the present study and, this can be related to environmental conditions since the south of Mozambique is more arid.…”
Section: Malaria Risk Mapping I Analytical Hierarchical Process and C...supporting
confidence: 78%
“…In Southern Africa the malaria decrease was between 50 to 91 %. In Mozambique the reduction is slow and, between 2015 and 2018, cases fall only by 14 % [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on a pediatric map of Hangzhou also found that AURI was the top disease discussed in all the outpatient visits they considered. However, the next most popular category of diseases in their study was common symptoms, such as fever, abdominal pain, and vomiting, which was distinct from the pattern we found in the online health service [ 38 ]. Internet hospitals provide a way to efficiently and conveniently acquire knowledge about children’s growth and development, relieving parents’ anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…Childhood cancer is a rare disease. Cancer does not fall into the top 100 of the most-reported paediatric diseases encountered across outpatient visits in a children's hospital (1). Despite being rare, childhood cancer remains a major public health issue in Europe (2).…”
Section: Introductionmentioning
confidence: 99%
“…Series of population-based EUROCARE-5 studies demonstrate that survival rates of childhood cancer in Lithuania are 10-20% lower than the European mean (4)(5)(6). Poorer outcome indicators were related to the inferior health expenditure in the country (below 2,000 USD per capita 1 ) and restricted access to international funding aimed at supporting research activities and collaboration (7). Incomplete cancer registration could partially contribute to inferior survival estimates (8).…”
Section: Introductionmentioning
confidence: 99%